Operators of Generalized Translation and Hypergroups Constructed from Self-Adjoint Differential Operators - Kosyak, O. V.; Nizhnik, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We construct new examples of operators of generalized translation and convolutions in eigenfunctions of certain self-adjoint differential operators.